2000
DOI: 10.2136/sssaj2000.6441525x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphorus Loading on Organic Nitrogen Mineralization of Everglades Soils

Abstract: There have been recent concerns about the anthropogenic phosphorus (P) loading to the naturally oligotrophic Everglades ecosystem. We investigated the effect of P loading on the biogeochemical cycling of nitrogen (N). We investigated the distribution of the potentially mineralizable N (PMN) rate as an indicator of the influence of P loading on selected microbial activities in soil and detritus layers. Soil characteristics measured included bulk density; total C, N, and P; microbial biomass C; and N and extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(78 citation statements)
references
References 46 publications
(46 reference statements)
3
74
1
Order By: Relevance
“…Some authors have suggested that the inclusion of P in the fertilizer may stimulate N cycling (Bennett et al 2003) and increase rates of N mineralization (Côté et al 2000;White, Reddy 2000;Carlyle, Nambiar 2001). Our study showed that both N and P were necessary for the volume response observed at granitic and sandy sites.…”
Section: Discussionsupporting
confidence: 55%
“…Some authors have suggested that the inclusion of P in the fertilizer may stimulate N cycling (Bennett et al 2003) and increase rates of N mineralization (Côté et al 2000;White, Reddy 2000;Carlyle, Nambiar 2001). Our study showed that both N and P were necessary for the volume response observed at granitic and sandy sites.…”
Section: Discussionsupporting
confidence: 55%
“…By this mechanism, isotopically light forms of organic N are preferentially mineralized, leaving the residual organic N in the soil system isotopically heavier (Fogel and Tuross 1999). If P loading of WCA-2A stimulated organic N mineralization and associated loss processes, this theory would predict that the d 15 N of soil organic matter would gradually increase near inflows, leading to a similar, gradual d 15 N increase in the macrophyte communities utilizing mineralized soil N. This may be the case in the Everglades where additions of P to the highly P-limited soil do stimulate microbial activities with a concomitant increase in both N mineralization and NH þ 4 flux (White and Reddy 2000). Despite the plausibility of this argument, however, such a mechanism fails to explain the different responses of Typha and Cladium growing along an identical eutrophication gradient.…”
Section: Resultsmentioning
confidence: 98%
“…Increasing interest has been focused on the role of freshwater wetlands, particularly northern peatlands, as C sinks (White and Reddy 2000;Clair et al 2002;Chmura et al 2003), because these wetlands store about one-third of the global terrestrial soil organic C (SOC) of 1395 Gt (Post et al 1982). Changes in N and P in wetland ecosystems have also received attention, since they are important nutrients for plant growth (Mitsch and Gosselink 2000).…”
Section: Introductionmentioning
confidence: 99%